Halalpreneur Opportunities and Challenges: Empirical Evidence from Indonesia - Ayatullah Sadali; Muhammad Khoirul Fikri; Hendri Hermawan Adinugraha (Al-Intaj)
Purpose: This research aims to explain the business opportunities and challenges of the halal industry in Indonesia for Halalpreneurs